2020
DOI: 10.11622/smedj.2019156
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative anaphylaxis and investigations: a local study in Hong Kong

Abstract: CONCLUSION Proper workup after an intraoperative anaphylactic event has a fairly good chance of identifying the causative allergen. These results are useful for patient management and the planning of subsequent anaesthetic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The analysis of our registry did not reveal significant differences between the incidence of reactions induced by penicillin and cephalosporins, probably because of the small size of the analysed groups. Anaphylaxis due to cefuroxime (cefuroxime axetil) was rarely reported [52,54], but this is not true for our registry and data from Hong Kong [27]. Other classes of antibiotics caused anaphylaxis in single patients.…”
Section: Causes Of Anaphylaxismentioning
confidence: 60%
See 1 more Smart Citation
“…The analysis of our registry did not reveal significant differences between the incidence of reactions induced by penicillin and cephalosporins, probably because of the small size of the analysed groups. Anaphylaxis due to cefuroxime (cefuroxime axetil) was rarely reported [52,54], but this is not true for our registry and data from Hong Kong [27]. Other classes of antibiotics caused anaphylaxis in single patients.…”
Section: Causes Of Anaphylaxismentioning
confidence: 60%
“…Most men and women with anaphylaxis developed cutaneous (75% and 78%), cardiovascular (71% and 74%), and respiratory (59.6% and 72.5%) symptoms. However, the data acquired from the research on perioperative anaphylaxis (according to a local study in Hong Kong) indicated cardiovascular manifestation as the one which occurs most often in this group (87, 3%) [27]. Only 12% of children did not have cutaneous symptoms in the conducted research, just like in the case of Poowuttikul [28], as compared to more than 20% in adults.…”
Section: Clinical Manifestationsmentioning
confidence: 84%
“…Recent studies showed that the incidence of POA is higher than thought (Au et al 2020 ). As the included patients were from different hospitals, this study was not able to provide the incidence of POA in China.…”
Section: Discussionmentioning
confidence: 93%
“…Perioperative anaphylaxis (POA) is a rare but often a potentially life-threatening condition that can contribute significantly to the morbidity and mortality of surgical patients (Au et al 2020 ; Gonzalez-Estrada et al 2021 ; Mertes et al 2019 ). It is reported that the estimated worldwide incidence of POA varies from 1 in 1250 to 1 in 20,000 procedures, with a mortality rate of 4%, and an additional 2% surviving with severe brain damage (Gandhi et al 2017 ; Mertes et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Essa reação inicia-se com congestão venosa propiciando a redução do retorno venoso e subsequente ativação dos receptores mecanossensoriais, sentidos que ativam o nervo vago e causam redução da frequência cardíaca, vasodilatação excessiva e possível perda da consciência. A síncope vasovagal é mediada por reflexos que incluem pródromo de tonturas, com ou sem náuseas, palidez e/ou sudorese (Au, Lau, Lam & Chan, 2020). Ainda, há outras causas com menores semelhanças, como os quadros de bradicardias provocados por betabloqueador, que apesar de menos frequentes ainda necessitam de um diagnóstico diferencial assertivo.…”
Section: Diagnóstico E Diagnóstico Diferencialunclassified